Nitti års norsk hvalfangst - Bogen, Hans (Norge på havet, 1954)
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; skipsfart

Sandefjord og Sandar de siste 30 år - Lind, Ole (Sandefjord kommunale handelsgymnasium og handelsskole : 1904-1954, 1954)
Keywords: Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangstindustri; hvalindustri

Norges skibsførere : 1935-1953 - Meling, Torjer (red.); Berg, Gabriel (red.); Bjønness, Henry (red.); Lindtner, N Fr. (red.) (Dreyer, 1954)
Keywords: Nordmenn; Sørishavet; biografier; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk; skipsfart; skipsførere

Hval og mannfolk - Robertson, R B; Stai, Arne (Gyldendal, 1954)
Keywords: Nordmenn; Sørishavet; ekspedisjon; hvalfangere; hvalfangst; pelagisk; sjøfolk

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann